Electric-field control of single-molecule tautomerization. Issue 11 (6th March 2020) - Mangel, Shai; Skripnik, Maxim; Polyudov, Katharina; Dette, Christian; Wollandt, Tobias; Punke, Paul; Li, Dongzhe; Urcuyo, Roberto; Pauly, Fabian; Jung, Soon Jung; Kern, Klaus
Abstract : The combination of a graphene field-effect transistor and a gate-tunable scanning tunneling microscope enables independent control over the electric field. Using this method, we studied the electric field effect on the tautomerization reaction. Abstract : The electric field is an important parameter to vary in a single-molecule experiment, because it can directly affect the charge distribution around the molecule. Yet, performing such an experiment with a well-defined electric field for a model chemical reaction at an interface has proven to be extremely difficult. Here, by combining a graphene field-effect transistor and a gate-tunable scanning tunneling microscope (STM), we reveal how this strategy enables the intramolecular H atom transfer of a metal-free macrocycle to be controlled with an external field. Experiments and theory both elucidate how the energetic barrier to tautomerization decreases with increasing electric field. The consistency between the two results demonstrates the potential in using electric fields to engineer molecular switching mechanisms that are ubiquitous in nanoscale electronic devices.